Analysis of the Auction Mechanism for Rahn Collateral in Islamic Pawnshops - Abd Mukit; Firman Setiawan (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
The auction mechanism for pledged goods (rahn) in Islamic pawnshops represents a crucial intersection between Sharia compliance and the application of Islamic business ethics. This study aims to critically examine the auction procedures at Pegadaian Syariah Blega Branch and assess their conformity with core ethical values in Islamic economics. Employing a qualitative descriptive method, data were gathered through direct observation, semi-structured interviews with both employees and customers, and document analysis. The results indicate that the auction process is carried out in a transparent and professional manner, involving key stages such as item reappraisal, formal customer notification, public auction announcements, and an open and competitive bidding system. These procedures align not only with fiqh provisions concerning rahn but also reflect fundamental Islamic ethical values, including honesty (á¹£idq), justice (â€˜adÄlah), and trustworthiness (amÄnah). The study concludes that the auction mechanism implemented at Pegadaian Syariah Blega Branch is not merely compliant with the formal legal framework but also serves as a concrete embodiment of Sharia-based ethical business practices. This contributes meaningfully to strengthening ethical governance within Islamic financial institutions and underscores the importance of integrating moral values into operational mechanisms.